The impact of brand authenticity on brand advocacy, through brand trust and consumer-brand identification mediators, in Turkey - Başar, Evren Dağ (My University, 2020)
Bu çalışma, günümüzde ilişkisel pazarlamaya yapılan yatırımın önemini ve güvene dayalı ve gerçekçi müşteri-marka ilişkisinin gerekliliğini dikkate alarak, mevcut literatür çalışmalarınca marka güveni sağladığı ve müşteri-marka arasında duygusal bağ kurduğu tespit edilen Marka Gerçekliği kavramını merkeze alarak kurgulanmıştır. Marka Gerçekliği, pazarlama literatüründeki en yeni kavramlardan bir tanesidir ve 2000’li yılların ortalarından itibaren dünya çapında artan sayıda akademik çalışmaya konu olmuştur. Çalışmanın öncelikle amacı kendisini içsel olarak gerçek olarak konumlandıran bir markanın sağlayacağı güçlü müşteri-marka ilişkisini incelemek ve Marka Gerçekliğinin kazanımı olarak müşteri ve marka faydalarını sorgulamaktır. Test edilen yapılar arasındaki bu ardışık ilişki vurgulanarak, mevcut literatüre Marka Güveni ve Müşteri-Marka kimliklendirmesi yapılarının, Marka Gerçekliği ve Marka Savunuculuğu arasında aracılık etkisi olarak kullanıldığı yeni bir model kazandırılmıştır. İlave olarak Marka Savunuculuğu ilk kez bir Marka Gerçekliği çalışmasında sonuç olarak çalışılmıştır. Global literatürde bir süredir Marka Gerçekliği çalışmaları yapılıyor olsa da Türkiye temelli akademik çalışmalar henüz çok kısıtlı olduğu için, konu yeni bir coğrafi alana doğru genişlemiş bulunmaktadır. Bu çalışmanın tamamlayıcı hedefleri olarak yapının Türkçe tanımı sorgulanmış ve bu kavrama göre derecelendirilmiş Türkiye’deki ilk marka listesi oluşturulmuştur. Tüm bu hedefler ile Marka Gerçekliği literatürüne katkıda bulunulması, literatürün genişletilmesi ve araştırmacıların konu hakkında dikkatinin çekilmesi amaçlanmıştır. Çalışmanın yöntemine karar verilmeden önce, mevcut literatür 70’den fazla çalışma kapsamında kavramın tanımı, yapısı, öncülleri ve ardılları başlıkları ile ve araştırma modeli, yöntem ve örneklem özellikleri anlamında incelenmiştir. Yöntem seçiminde birbirine takip eden dört farklı çalışma yapılmış ve ana araştırma aracı 400 kişilik bir örneklem üzerinde, Ocak 2020’de, profesyonel bir çevrimiçi araştırma platformu aracılığı ile test edilmiştir. Toplanan verilerin modelin test edilmesi için Yapısal Eşitlik Modeli kullanılmıştır. Bulgular, tüm yapılar arasındaki olumlu ilişkiyi ve Marka Güveni ve Müşteri-Marka Kimliklendirmesinin aracılık etkisi göstererek, Marka Gerçekliği'nin Marka Savunuculuğu üzerindeki yüksek dolaylı etkisine ışık tutmaktadır. İlave olarak, örneklem grubumuz ‘Gerçek’ ifadesini yapının Türkçe tanımı olarak belirlemiş ve derecelendirilmiş marka listesi oluşturulmasını sağlamıştır. Tüm bu bulgular ve literatür taraması baz alınarak, akademik ve yönetimsel sonuçlar da çalışmanın son bölümlerinde okuyucu ile paylaşılmıştır.

Underpinned from the fact that investing in relationship marketing is crucial for companies and brands today, and the demand for trustworthy and truthful consumer-brand relationship is rising, this study took brand authenticity as the core construct that is stated to create trust and enhances emotional bonds between the consumer and the brand in the prior literature studies. Brand Authenticity is one of the most recent constructs in marketing literature and there has been increasing number of academic studies worldwide since mid 2000s. The initial purpose of this study was to examine strong consumer brand relationship benefits when a brand intrinsically positions itself as authentic and the sequential consumer and brand benefits of brand authenticity. Aimed at stressing the casual relationship between the constructs, we aimed to contribute and extend the literature through a new model which tested the mediation effects of Brand Trust and Consumer-Brand Identification between Brand Authenticity and Brand Advocacy. Testing both mediators in a Brand Authenticity study as well as testing Brand Advocacy as an outcome construct is new to the Brand Authenticity literature. Eventhough there have been models tested in the global literature, the construct demonstrated a less tapped area in the academic research in the Turkish culture; therefore, we extended the literature to a new geographic location. The complementary objectives of this study was to find a Turkish definition of Brand Authenticity as there are different usages in the few academic studies, and to find the first authentic brand rating in the Turkish culture and comparing it with global ratings. All of these objectives aimed at contributing and extending the Brand Authenticity literature and taking researchers’ further attention. Before studying on the methodology and reaching our model, it was critical for us to understand the Brand Authenticity construct from all angles. Therefore, we examined the literature on definition, conceptualization, antecedents and attributes, further cues, and consequences of brand authenticity. While examining more than 70 studies, we explored each of the studies’ model, methodology and sample characteristics to understand the current situation in the existing literature. We used four sequential stages in the methodology with exploratory and descriptive techniques to achieve our research objectives. We conducted the main research instrument on 400 people in January 2020, through a professional online survey panel and the gathered data is analysed by Structural Equation Modelling. The findings revealed the positive relationships between all constructs and Brand Trust and Consumer-Brand Identification as intermediate in the casual sequence such that the indirect effect of Perceived Brand Authenticity is higher on Brand Advocacy when the mediators exist. Furthermore, our sample defined authentic brand as “gerçek” and proposed an authentic brand rating. Grounding from the literature survey and new findings, the managerial and academic implications were presented as well in the final sections.
Keywords: Brand Advocacy; Brand Trust; Business; Consumer Brand Identification; Consumer Brand Relationship; İşletme; Marka Gerçekliği; Marka Güveni; Marka Savunuculuğu Brand Authenticity; Marka-Müşteri İlişkisi; Marka-Müşteri Kimliklendirmesi; Marketing; Pazarlama; Production management; Üretim yönetimi